Construction of Standard Fast Medical Procedures for Traumatic Shock and Its Application Effects - Yan Wang; Siqi Luo (Emergency Medicine International)
Objective. To explore the construction of standard fast medical procedures for traumatic shock and its application effects. Methods. 84 patients with traumatic shock were admitted to emergency department of the hospital between January 2018 and January 2020. Using random number table method, the patients were divided into the control group (was given emergency treatment by routine emergency rescue procedures) and the study group (was given emergency treatment by standard fast medical procedures) with 42 patients in each group. The treatment time (rescue time, consultation time in each department, and examination time), shock index (SI), blood pressure fluctuation range, urine output, serum lactate (LAC) level, activated partial thromboplastin time (APTT), and international normalized ratio (INR) were recorded. The incidences of complications in the two groups within 3 days were counted. Results. The rescue time, consultation time, and examination time of the study group were shorter than those of the control group (P<0.05). After 18 h of treatment, the SI, blood pressure fluctuation range, LAC, and APTT in the study group were lower or shorter than those in the control group (P<0.05), while urine volume and INR were higher than those in the control group (P<0.05). Within 3 days of treatment, the incidence of complications in the study group was 5.41% lower than that in the control group which was 24.14% (P<0.05). Conclusion. Standard fast medical procedures can effectively shorten the time of each stage of emergency treatment for traumatic shock, which allows patients to receive effective treatment in the shortest time while improving shock symptoms and reducing related complications.